Young users of social media: an analysis from a gender perspective - Aran-Ramspott, Sue; Korres-Alonso, Oihane; Elexpuru-Albizuri, Iciar; Moro-Inchaurtieta, Álvaro; Bergillos-García, Ignacio (Frontiers in Psychology, 2024)
One of the major challenges for edu-communication research is to analyse the influence of social media on young and adolescent users. This article examines the evaluation of gender inequalitiesreal and symbolic -in the consumption of social networks such as YouTube and Instagram among young people. Within the framework of a Research & Development & innovation (R&D+i) project, it presents a discursive-theoretical analysis of how young users of social media perceive the presence and representation of gender on social media and whether such digital representations can be associated with an empowering gender perspective. This study presents results from 14 focus groups (N= 83), composed of students aged 12 to 18, drawn from three Spanish Autonomous Communities (Catalonia, the Balearic Islands and the Basque Country). The results show that gender issues arise in participants' conversations, especially among female participants, who perceive the importance of physical appearance on platforms such as Instagram and TikTok. Female participants feel more pressure in terms of appearance and dress compared to male participants. Among male participants there are more expressions of self-affirmation and more mentions related to fun and social prestige. Both male and female participants express concern about the impact of that pressure on younger girls. The influence of social media on self-image is more evident among female participants, who make frequent mention of the importance of self-esteem in relation to beauty standards and exposure to idealised body images. Notably, there were no comments by male participants that acknowledge any influence of social media on their self-image. The findings are in line with existing research and taken as a whole gives rise to concern as to the gender disparities observed in the use of social media, which do not constitute a picture of female empowerment. This research underlines the importance of promoting a respectful and equitable environment in relation to gender equality within digital spaces. Thus, this study provides support for the need to develop and implement edu-communicative initiatives to foster critical thinking around the influence of social media in this context and the evaluation of the impact of such initiatives in future research.